Dutch design 2004-2005 - Beroepsorganisatie Nederlandse Ontwerpers (Amsterdam : Bis, 2004)
This is the 8th edition of BIS Publishers' successful Dutch Design showcase series, published in collaboration with BNO, the Association of Dutch Designers. Over 400 (!) Dutch designers present themselves with their best and most recent work. This edition comprises two hardbound volumes. The use of top grade paper, a variety of printing inks, UV varnish for the hardback covers and an overall rich and colourful design, ensures that this publication appeals to designers throughout the world who find inspiration in Dutch experiment and creativity. The Dutch Design series has received wide acclaim for its very complete survey of design in Holland, and as a result, has become a collector's item in the Netherlands and abroad. Volume I concentrates mainly on the work of graphic designers, with more concise sections devoted to packaging and illustration design. Volume 2 highlights the work of designers active in the fields of product, interior, retail, exhibition and new media design. All these books have a highly visual appeal. They provide the reader with an enormous input of ideas and examples of new and challenging design from the Netherlands.
Dl.X: Graphic design, packaging design, illustration. Dl.Y: Industrial design, experimental design, environmental design, interactive media.
Keywords: Industrieel ontwerpen; Industriële vormgeving